The Role of the Land Office in Supervising the Making of Land Deeds by Officials Making Temporary Land Deeds in Banyumas Regency - Yulianto, Annisa Rahmalia (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2024)
Banyumas Regency has 134 active Land Deed Officials, but due to the large area and many remote areas, the sub-district head is mandated by law as a substitute for the PPAT and is spread across 27 sub-districts in Banyumas Regency. BPN in this case also plays a role in supervision related to the PPATS carried out by the sub-district heads as general officials. The purpose of this study is to analyze the role of the National Land Agency in supervising the making of land deeds by Temporary Land Deed Officials in Banyumas Regency and to analyze what obstacles hinder supervision and provide solutions to the making of land deeds by Temporary Land Deed Officials in Banyumas Regency. The approach method in this study is sociological juridical. The data used are primary and secondary data obtained through interviews and literature studies, data analysis is carried out descriptively analytically, and the theory used is the theory of legal certainty and legal protection. The results of the study and the conclusions that can be obtained are: 1. The National Land Agency (BPN) has the authority to carry out guidance and supervision. The basis of the supervisory authority in general for the land environment refers to the duties and functions of the National Land Agency (BPN), while the basis of the supervisory authority is more related to the supervision of Land Deed Officials (PPAT) and Temporary Land Deed Officials (PPATS). This is regulated in the Regulation of the Minister of Agrarian Affairs and Spatial Planning Number 2 of 2018 concerning the Guidance and Supervision of Land Deed Officials. 2. The Banyumas Regency Land Office revealed that there were violations of regulations committed by a number of Temporary Land Deed Officials PPATS. These violations include late monthly reporting, inaccurate deed contents, and the use of inappropriate PPATS letterheads. The impact of these violations can create land disputes, hinder the process of achieving legal certainty, and harm the community. To overcome this problem, the Head of the Regional Land Office provides guidance and supervision of PPATs in administration and services to the community.Keywords: Authority; Land; Transfer.